Legal Protection of Genetic Research - Maneva, Veselina (Yearbook of the Law Department, 2020)
The article discusses the patentability of the results of genetic research, in particular the sequence of genes in the molecular structure of deoxyribonucleic acid. The main approaches established in the American, European and national legal system regarding the protection of genetic inventions are presented. The main points in a decision of the Court of Justice of the EU are analysed. Both the criteria for patentability of an element of the human body and the hypotheses referring to the exceptions to patentability corresponding to the provisions of Directive 98/44/EC on the legal protection of biotechnological inventions, the Convention on Human Rights and Biomedicine of Oviedo, the European Patent Convention and the TRIPS Agreement. The connection between the importance of genetic research and the development of the innovative economy based on the patents for these inventions is substantiated.